Fluid-structure interactions for the air blast loading of elastomer-coated concrete. (15th August 2019) - Fallon, C.; McShane, G.J.
Abstract: The fluid-structure interaction (FSI) effect experienced by an elastomer-coated concrete slab subjected to blast loading in air is studied numerically. The aim is to establish whether a flexible coating alters blast-structure interactions and whether this can explain the apparent blast mitigating capability of this retrofit solution as reported in published experimental investigations. Numerical models for a typical concrete and spray-on elastomer coating are established and a Coupled Eulerian–Lagrangian (CEL) model is employed to predict the air blast response. A 1D FSI analysis suggests that the elastomer coating increases the peak compressive stress in the concrete during short timescale pressure wave interactions. But the effect on the total imparted momentum is small, across a range of target mass and blast intensity. However, due to momentum sharing, the impulse imparted to the concrete plate is reduced in the coated configuration. By extending the analysis into 2D, it is found that the displacement of a concrete slab is marginally reduced when coated on either the blast-receiving or non-blast-receiving face. Thus, it is postulated that the elastomer contributes a small, beneficial mechanical effect. Finally, the need for a fully coupled (CEL) approach to model the blast-structure interaction is interrogated. For a wide range of cases, the results suggest that using a purely Lagrangian approach, in which a pressure-time history is directly applied to the structure (thereby neglecting full representation of FSI effects), is sufficient to capture the deflection behaviour of coated concrete plates. However, it is shown that the significance of the error associated with this simplification depends on the blast intensity and slab geometry under consideration.